Membangun Kesetaraan Gender Dalam Keluarga Karier - Ammar Asyqarul Azzam; Ahmad Rezy Meidina (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This writing seeks to explain how the role of the couple in building gender-based partnerships in the household. This writing uses a socio-cultural approach. Where, gender equality is not limited to the differences between men and women. However, how can the two of them build an equal relationship without marginalizing one another, especially women. In the area of ​​families who have careers or workers, the realization of gender equality can be achieved in various ways, especially the compromise of both partners to achieve their goals or aspirations together in the household. In fact, for now the working spouse has been able to start building a partnership with a good partner to realize the welfare of his family. This can be achieved by understanding each function and then making it happen by building good communication with your partner. Keywords: gender equality, family, career